Use of Dog Parks and the Contribution to Physical Activity for Their Owners. Issue 2 (2nd April 2016) - Evenson, Kelly R.; Shay, Elizabeth; Williamson, Stephanie; Cohen, Deborah A.
Abstract : Purpose: This study described the use of dog parks in several diverse locations and explored the contribution dog parks made to physical activity of the dog owners.Method: The Systematic Observation of Play and Recreation in Communities (SOPARC) tool was used to count the number and characteristics of people using parks. Observations were conducted 4 times per day, 4 days per week during for 1 week in 6 urban/suburban parks during different seasons. Collection sites included 3 dog parks in Chapel Hill/Durham, NC; 2 dog parks in Los Angeles, CA; and 1 dog park in Philadelphia, PA. Interviews at the NC and PA parks were conducted among 604 adults.Results: We counted 2, 124 people (11.9%) in the dog park area compared with 15, 672 people in the remaining park areas. Based on observations, dog park visitors were more likely to be female and White or Other race/ethnicity compared with Hispanics, and were less likely to be children or engaged in walking or vigorous activity. Park interviews revealed that compared with other park activities, reporting walking/watching a dog at the park was more common among those who visited the park more frequently ( ≥ 1 time per week), stayed at the park for a shorter time ( ≤  1 hr), or visited the park alone.Conclusion: Although dog parks may be an important destination for dog owners and contribute to physical activity, the contribution of dog parks to participants' moderate-to-vigorous physical activity was limited.